Characterization of a Ruthenium(II) Complex in Singlet Oxygen-Mediated Photoelectrochemical Sensing - Verrucchi, Margherita (Langmuir : the ACS journal of surfaces and colloids, 2023)
A water-soluble ruthenium(II) complex (L), capable of producing singlet oxygen (1O2) when irradiated with visible light, was used to modify the surface of an indium-tin oxide (ITO) electrode decorated with a nanostructured layer of TiO2 (TiO2/ITO). Singlet oxygen triggers the appearance of a cathodic photocurrent when the electrode is illuminated and biased at a proper reduction potential value. The L/TiO2/ITO electrode was first characterized with cyclic voltammetry, impedance spectroscopy, NMR, and Raman spectroscopy. The rate constant of singlet oxygen production was evaluated by spectrophotometric measurements. Taking advantage of the oxidative process initiated by 1O2, the analysis of phenolic compounds was accomplished. Particularly, the 1O2-driven oxidation of hydroquinone (HQ) produced quinone moieties, which could be reduced back at the electrode surface, biased at -0.3 V vs Ag/AgCl. Such a light-actuated redox cycle produced a photocurrent dependent on the concentration of HQ in solution, exhibiting a limit of detection (LOD) of 0.3 μmol dm-3. The L/TiO2/ITO platform was also evaluated for the analysis of p-aminophenol, a commonly used reagent in affinity sensing based on alkaline phosphatase